(untitled) (European Journal of Education and Psychology, 2019)
Learning Styles are a set of cognitive, physiological and affective traits that indicate how students perceive, interact and respond to different learning environments. Each student has their own learning style of acquiring knowledge. Students, in addition to using their cognitive skills and cognitive goals, must also know how to rank, organize and prioritize their learning. Although the study of learning styles is very common in the levels of compulsory education, there is less research in higher education. In this study, learning styles are recognized as essential teaching resources to guide meaningful learning. The study has been carried out with engineering university students. A descriptive, non-experimental and cross-sectional methodological design carried out in the Forest Engineering degree at the University of Pinar del Río (Cuba) was used. A total of 120 university students participated in the study (53.3% women and 46.6% men). Participants have completed the Honey-Alonso Learning Styles Questionnaire (CHAEA). The answers allowed to determine the profile of student learning styles. Data suggested that the reflexive style being the most representative, followed by the theoretical, active and pragmatic styles. No statistically significant differences in learning styles were detected between academic years for men, but they were detected for women. An evolution of the reflexive and theoretical styles is evidenced with the level of professionalization of the students as they move through the academic years. This evolution is being linked with the best academic performance achieved. The study evidenced that learning styles are a valuable resource that enriches the orientation of teaching in terms of diversity and the improvement of learning. Its effects on the training of engineers was analysed and strengths and weaknesses in the applied field of higher education was discussed.